2014
DOI: 10.11613/bm.2014.035
|View full text |Cite
|
Sign up to set email alerts
|

The many faces of estrogen signaling

Abstract: Estrogens have long been known as important regulators of the female reproductive functions; however, our understanding of the role estrogens play in the human body has changed significantly over the past years. It is now commonly accepted that estrogens and androgens have important functions in both female and male physiology and pathology. This is in part due to the local synthesis and action of estrogens that broadens the role of estrogen signaling beyond that of the endocrine system. Furthermore, there are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
258
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 326 publications
(265 citation statements)
references
References 92 publications
1
258
0
6
Order By: Relevance
“…However, there are also multiple soluble ER isoforms (e.g., ER-beta [Erβ]; ER-gamma) that can interact with ERα to influence tissuespecific expression of estrogenic effects [9]. Additionally, other estrogen-mediated responses may be mediated and/or influenced by affected by cell membrane localized, G-protein coupled ERs [10].The majority of the HTP assays proposed for the EDSP prioritization effort for estrogenic substances are based on mammalian-primarily human-ERs and predominantly measure different facets of chemical interaction with ERα specifically or multiple types of ERs non-specifically [11]. Consequently, since the overall endocrine screening and testing program is intended to protect both humans and wildlife [1, 2], a critical uncertainty involves the degree to which results from mammalianbased assay systems designed to detect potential estrogenic chemicals are translatable to other species of concern.…”
mentioning
confidence: 99%
“…However, there are also multiple soluble ER isoforms (e.g., ER-beta [Erβ]; ER-gamma) that can interact with ERα to influence tissuespecific expression of estrogenic effects [9]. Additionally, other estrogen-mediated responses may be mediated and/or influenced by affected by cell membrane localized, G-protein coupled ERs [10].The majority of the HTP assays proposed for the EDSP prioritization effort for estrogenic substances are based on mammalian-primarily human-ERs and predominantly measure different facets of chemical interaction with ERα specifically or multiple types of ERs non-specifically [11]. Consequently, since the overall endocrine screening and testing program is intended to protect both humans and wildlife [1, 2], a critical uncertainty involves the degree to which results from mammalianbased assay systems designed to detect potential estrogenic chemicals are translatable to other species of concern.…”
mentioning
confidence: 99%
“…Both ERa and ERβ can also regulate the transcription of genes through interaction with other transcription factors, including specific protein-1 (SP1), nuclear factor kappa-B(NF-kappaB), activator protein-1(AP-1), CCAAT/enhancer binding protein b (C/EBPb), GATAbinding protein 1(GATA 1), and signal transducer and activator of transcription 5 (STAT5), enabling the activation or repression of target genes, which significantly amplifies the regulatory influence of estrogen. 27,28 One of the best known examples of interaction between the ER and other transcription factors is that of the complex ER-estrogen with Finkel-Biskis-Jinkins (FBJ)-osteosarcoma homolog (FOS) protein and JUN protein at the DNA binding site of the transcription factor AP-1. It has been recently shown that the transcriptional activation of cyclin D1 occurs through binding of the complex ER-estrogen with the JUN protein in endometrial glandular cells.…”
Section: Genomic Signaling In Endometriosismentioning
confidence: 99%
“…The ER can be found on the surface of some cells in a complex that allows rapid responses, which are termed nongenomic signaling (48). This circumvents ER's more classical genomic signaling, which requires ER bound with ligand to dimerize and translocate from the cytoplasm to the nucleus, where the activated ER binds to specific DNA sequences (i.e., response elements), leading ultimately to gene transcription.…”
Section: Nongenomic Signaling By Membrane-associated Ersmentioning
confidence: 99%